Acht Geschichten über die Integrationsgeschichte Zur Grundlegung der Geschichte der europäischen Integration als ein episodisches historiographisches Erzählen - Pichler, Peter (Studien Verlag, 2011)
European integration represents a historically unprecedented and new form of a continent's peaceful unification. Therefore, historiography needs innovative theoretical concepts to illustrate this process appropriately; at the present moment, however, integration history is only characterized by an extensive 'theoretical deficit'. The book project 'Acht Geschichten über die Integrationsgeschichte. Zur Grundlegung der Geschichte der europäischen Integration als ein episodisches historiographisches Erzählen' critically adopts this opinion and illuminates the theoretical principles of integration historiography. A proposal regarding the theoretical principles of unification historiography is compiled from an interdisciplinary perspective. The concept of the episodic historiographic narrative (Peter Pichler) understands the unification of Europe as a comprehensive cooperation and transformation process in which various historic strands (e.g. political, economic, cultural, social, legal, religious, etc.) interlink with each other. Therefore it would be most sensible to show their totality as an episodic historiographic network within the historiographic context. This theoretical proposal shall be provided for research as a new meta-perspective and methodical tool. In a first step, the hitherto existing research on integration history is critically reviewed. Furthermore, its discourse will be analysed. Particular attention is paid to include Eastern and Southern European as well as Turkish perspectives. Their synopsis shows the interplay between the Eastern and Southern European 'transition'-narrative and the Turkish perspective on the integration process as the driving force of the debate. Furthermore, 'post-modern' perspectives on integration history represent an important feature of the discourse's acceleration and renewal. The first step ends with the contributors being able to give a first innovative impulse to the discursive renewal of research concerning integration history; the neoterised term 'transnarrative competence' allows for correlation between 'transition'-narrative and Turkish perspectives on integration. In a second step, those theoretical features from recent developments in integration and historical theory are isolated that can contribute to a perspective renewal of research. The concept of the episodic historiographic narrative proposes an interdisciplinary theory based on those elements of political, social, legal and cultural sciences. The analytical narrative mindset of each element is determined and thus reconstructed as one episodic plot line, one episode of European integration history. The net of episodes eventually constitutes the proposed theory of an episodic historiographic narrative. Thus, the concept of the episodic historiographic narrative does not only enable histrorians to overcome the deficit in the theory of integration historiography but also enters new academic ground by uniting interdisciplinary elements to an episodic network.